DIVERSITAS SERANGGA PADA HUTAN TANAMAN MONOKULTUR DAN HUTAN HETEROGEN DENGAN METODE WINDOW TRAPS - Irham Falahudin; Jasmi; Siti Salmah; Dahelmi (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2011)
Insects are a very important role in an ecosystem. Among these roles are: herbivori, predation, parasitism, decomposition, pollination, and so on (Speight et al., 1999). In addition to the role of insects have been used as an indicator species. Several recent studies (Davids, 2000; Talvi, 2000; Castillo and Wagner, 2002; McGeoch, 1998 & 2002) shows that insects have a response that indicates the extent of damage to forest habitat. To see how much effect the change will see the diversity of insects flying at both locations using the window trap. This method was chosen because it will look at the role of flying insects that can be used as indicators of changes in land to the stratification of the existing trees at both locations. The expected goal in this study were 1) To determine the level of insect diversity in both forest site 2) To determine the effect of changes in forest insect conditions in each forest stratification. From this research it was found that it contained the highest density of heterogeneous forests there are 29 families of 41 species and 119 individuals from arrest (day and night) while in monoculture forests with 32 species of 22 families and 98 individuals in which the degree of diversity between the forest with a monoculture in the heterogeneous forest monoculture forests range 2.14 <H <2.84. Whereas in heterogeneous forests ranges between 2 <H <3 and the third similarity index was not significantly different strata.